Makna Perkawinan Adat Dayak Bahau Busang dan Perkawinan Menurut Iman Katolik (Studi Komparatif dalam Perspektif Antropologi) - Iriene Paskalia Lunau; G. Simon Devung; Zakeus Daeng Lio (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2018)
The study aimed to comprehend the ceremonies and symbols (artifacts, activities and verbal expressions) used in the Customary Wedding Rite of the Bahau Busang Dayak and in the Wedding Celebration of Catholic Church, and disclose the meanings of the ceremonies and symbols (artifacts, activities and verbal expressions) used in the Customary Wedding Rite of the Bahau Busang Dayak and in the Wedding Celebration of Catholic Church, showing the similarities and differences found in Customary Wedding Rite of the Bahau Busang Dayak and in the Wedding Celebration of Catholic Church. The results of the research show that the Wedding Celebration of the Catholic Church and the Customary Wedding Rite of the Bahau Busang Dayak share some similarities and have differences, seen from the processions of the Celebration and Rite, and from the symbols being used. A good comprehension of those similarities and differences would enable the members of the Bahau Busang Dayak communities to have their faith in the Catholic religion with the apprehension of similarities of the religion values and the customary values. The similarities could bee seen from the same meaning and purpose to reach marriage happiness and loftiness in the fulfilment of their life and faith in God. Practically the findings of this minor thesis are expected to be used as the materials for the preparation of Catholic Catechesis for the Bahau Busang Dayak communities.